2018
DOI: 10.1039/c8ta06025h
|View full text |Cite
|
Sign up to set email alerts
|

Antisolvent processing of lead halide perovskite thin films studied by in situ X-ray diffraction

Abstract: The conversion mechanism from the precursor ink to the perovskite film using antisolvent-induced crystallization has been studied using in situ X-ray diffraction during blade coating and antisolvent deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 31 publications
1
59
0
Order By: Relevance
“…To understand the crystallization dynamics and antisolvent mechanism of CsPbI 3 , the as‐quenched films prior to annealing were first studied. It has previously been shown that the formation of a crystalline intermediate, typically light brown, precursor phase is critical in forming high‐quality, pinhole‐free films . Without an antisolvent, the CsPbI 3 as‐quenched, preannealed film retains a yellow color with an absorption onset of 450 nm ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…To understand the crystallization dynamics and antisolvent mechanism of CsPbI 3 , the as‐quenched films prior to annealing were first studied. It has previously been shown that the formation of a crystalline intermediate, typically light brown, precursor phase is critical in forming high‐quality, pinhole‐free films . Without an antisolvent, the CsPbI 3 as‐quenched, preannealed film retains a yellow color with an absorption onset of 450 nm ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 96%
“…These antisolvent physical parameters specifically do not account for any sort of adduct formation such as PbI 2 –DMSO, which has been identified to strongly influence the crystallization dynamics in halide perovskites . Basicity scales like the Gutmann's donor notionally account for the strength of adduct formation, but is based on adduct formation with a model Lewis acid (SbCl 5 ) and does not account for hardness or softness of the constituents thus is incomplete .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations